2004
DOI: 10.1292/jvms.66.1311
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Sweet Receptor Protein, T1R3, in the Human Liver and Pancreas

Abstract: ABSTRACT. The expression of T1R3, a taste receptor essential for the perception of sweetness and umami-taste, was examined by immunohistochemistry to determine whether and where it may be localized in the liver and pancreas. In the liver, both immunopositive and immunonegative reactions were detected; bile ducts and intercalated portions of the bile ductules were immunopositive to T1R3, while arterioles and venules were immunonegative in interlobular connective tissue. In the hepatic lobule, all other cells in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 20 publications
0
39
0
1
Order By: Relevance
“…The T1R genes were found in testis (91,92,120), brain, thymus (120), gastrointestinal tract, enteroendocrine cells (24,53,120,146), kidney, lymphocytes (92), liver, and pancreas (158). The T2R genes were found in testis (118), gastrointestinal tract, enteroendocrine cells (146,174,175), and nasal respiratory epithelium (55).…”
Section: Aqp5mentioning
confidence: 99%
“…The T1R genes were found in testis (91,92,120), brain, thymus (120), gastrointestinal tract, enteroendocrine cells (24,53,120,146), kidney, lymphocytes (92), liver, and pancreas (158). The T2R genes were found in testis (118), gastrointestinal tract, enteroendocrine cells (146,174,175), and nasal respiratory epithelium (55).…”
Section: Aqp5mentioning
confidence: 99%
“…T1R2-T1R3 is expressed in many tissues throughout the body, including the intestine , liver (Taniguchi 2004), pancreas (Taniguchi 2004), adipocytes (Masubuchi et al 2013), and brain (Ren et al 2009). T1R2-T1R3 agonists enhance intestinal glucose absorption ), incretin response (Brown et al 2009), insulin secretion (Pepino et al 2013), and adipocyte differentiation (Masubuchi et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the T1R family is also expressed in the small intestine and colon. Furthermore, Taniguchi (2004) showed that T1R3 is expressed in the intrahepatic bile duct and pancreas. Thus, the T1R family is expressed in various parts of the digestive system, and it is possible that these receptors may play a role in chemical sensations in these tissues.…”
Section: Discussionmentioning
confidence: 99%